2000
DOI: 10.1159/000027497
|View full text |Cite
|
Sign up to set email alerts
|

Ritleng Intubation Set: A New System for Lacrimal Pathway Intubation

Abstract: Silicone tubing of the lacrimal pathway is used after lacrimal pathway injuries or canalicular stenosis. This procedure is often complicated by the so-called accordeon phenomenon. Far the last 3 years we have used a new system for lacrimal intubation: the Ritleng intubation set. It consists of a silcone tube which is connected to a polypropylene tube and a specially designed stainless probe for lacrimal insertion. Due to the smooth connection of the polypropylene tube and the silicone tube intubation can be pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…In CCO, silicone intubation is also used in treatments involving laser canaliculoplasty 17 and external DCR with membranectomy, 18 and a variety of silicone intubation sets have been described. 12,14,15,[24][25][26] The probes have blunt tips to avoid submucosal penetration and injury to the lacrimal mucosa; however, blind insertion is required. We revealed that conventional methods of tube insertion have a high associated risk of submucosal penetration (20%), 12 and a quarter of CCO cases have severe ductal stenosis, which makes blind intubation diffi cult.…”
Section: Discussionmentioning
confidence: 99%
“…In CCO, silicone intubation is also used in treatments involving laser canaliculoplasty 17 and external DCR with membranectomy, 18 and a variety of silicone intubation sets have been described. 12,14,15,[24][25][26] The probes have blunt tips to avoid submucosal penetration and injury to the lacrimal mucosa; however, blind insertion is required. We revealed that conventional methods of tube insertion have a high associated risk of submucosal penetration (20%), 12 and a quarter of CCO cases have severe ductal stenosis, which makes blind intubation diffi cult.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Prior to this publication, what has not been reported is the potential for the device to break during intra-operative use on patients. To mitigate this complication, we discuss why this may have occurred and ways to prevent it in the future.…”
Section: Discussionmentioning
confidence: 99%
“…5 In 1996, Pierre Ritleng, a French specialist in oculoplastic and lacrimal surgery, first described a new system for nasolacrimal duct intubation developed to minimize mucosal injury. 6 The Ritleng probe (model S1-1470; manufactured by FCI Ophthalmics, Marshfield Hills, MA, U.S.A.) is a malleable, hollow, stainless steel tube with a diameter of 1 mm and a length of 105 mm. 5 The probe's superior end has a funnel-shaped entrance allowing easy introduction of the silicon stent's Prolene lead.…”
mentioning
confidence: 99%
“…The two silicone tubes were tied together with a polypropylene 6-0 suture and was fixated to the lateral wall of the nose. 12 In group 2, bicanalicular silicone tube intubation, according to Ritleng, was performed directly after probing.…”
Section: Between April 1 2000 and December 31 2005 We Includedmentioning
confidence: 99%